Delivering the visitor experience how to create, manage and develop an unforgettable visitor experience at your museum - Mackay, Rachel (Facet Publishing, 2023)
Visitor experience has been a long neglected aspect of museum practise, receiving less academic attention than areas such as exhibition design or collections care. Despite this, the quality of the visitor experience is the single biggest factor which will influence visitors returning to your museum, or recommending a visit to friends or family. It is also the area of museum practise that has undergone the biggest change in the last twenty years. The image of the aged security warder shouting at children to not touch the exhibits has long gone. Now, museum visitors expect teams of friendly, knowledgeable and passionate people ready to engage them with the museum in an interactive and enthusiastic way. Expectations have never been higher, and as they grow, museums must develop the visitor experiences they deliver in order to meet them. The book discusses the process of delivering a visitor experience from beginning to end; from opening a new visitor offer and building a team through to future planning and strategies for development. It draws from theories from practitioners and academics, arguing that by examining issues such as motivation and relevance, museum operators can start to truly put themselves in their visitors' shoes and build experiences that are impactful and unforgettable